A new reading of Binchois's Mon seul et souverain desir. Issue 2 (25th September 2015) - COOK, KAREN M.
ABSTRACT The copyist of the manuscript Oxford, Bodleian Library, Canon. Misc. 213 was detailed and well versed in numerous notational styles, and as a result, examples of unusual notation in this manuscript have drawn a critical eye. Yet the unique transcription of Binchois's rondeau Mon seul et souverain desir, in which the copyist alternates between the two common note shapes for the semiminim in the cantus voice, has thus far gone unexplained. This notation has no rhythmic significance; as such, it appears to be a superficial anomaly. In this article, I lay out a rationale for a reading of the notation of the semiminims in this piece as potentially deliberate and meaningful. Over the course of compiling the manuscript, the copyist increasingly aligned semiminim shape with prolation: the full-black shape is used exclusively in minor prolation, whereas the void flagged shape becomes more frequently restricted to major prolation. Since the rondeau is in minor prolation, I suggest that the copyist might have used the void flagged figure in order to suggest a momentary shift into major prolation. In so doing, the copyist might have left to us a witness of a performance practice in which the mensural and rhythmic possibilities inherent in the built-in tension between <private-char><inline-graphic xlink:href="ark:/27927/pgkg3fq1mg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></private-char> and <private-char><inline-graphic xlink:href="ark:/27927/pgkg3fq1wm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></private-char> were explored.